Analisis Penerapan Kompensasi Dalam Meningkatkan Kinerja Karyawan Terhadap Koperasi TKBM - Siti Sahara; Ryan Besta Dwiprasetya (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2023)
The aim of this research is to explain whether there is a significant influence of compensation on the performance of TKBM cooperative employees. Apart from that, this research also aims to determine employee performance. The type of research used by researchers is descriptive (descriptive research) using observation and questionnaire research methods. The author uses quantitative research techniques because researchers use statistical tools to manage questionnaire results. Data collection was carried out through observation and questionnaires and the data analysis method used descriptive analysis.